2020
DOI: 10.1002/brb3.1740
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency transcranial magnetic stimulation protects APP/PS1 mice against Alzheimer’s disease progress by reducing APOE and enhancing autophagy

Abstract: Introduction The repetitive transcranial magnetic stimulation (rTMS) has clinically wide application prospect of psychiatry and neuroscience, for its painless, noninvasive, and high efficiency. So far, rTMS has been used in the treatment of Alzheimer's disease (AD) but the underlying mechanism is not clear. Methods and Results The APP/PS1 mice at 3‐month‐old were treated by 5 Hz high‐frequency (HF) rTMS for two weeks. After rTMS treatment, the AD‐like cognitive impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(31 reference statements)
5
13
0
Order By: Relevance
“…The reduction of Aβ deposits by rTMS could be mediated by two processes: reduced Aβ production and/or facilitated Aβ clearance. Indeed, consistent with previous reports [ 8 , 47 , 65 ], we observed a significant reduction in the intraneuronal Aβ levels in the mPFC, dHC and S1 cortex, indicating that rTMS treatment suppressed Aβ production (Fig. 2 c).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The reduction of Aβ deposits by rTMS could be mediated by two processes: reduced Aβ production and/or facilitated Aβ clearance. Indeed, consistent with previous reports [ 8 , 47 , 65 ], we observed a significant reduction in the intraneuronal Aβ levels in the mPFC, dHC and S1 cortex, indicating that rTMS treatment suppressed Aβ production (Fig. 2 c).…”
Section: Resultssupporting
confidence: 93%
“…Our findings are in agreement with previous reports, that rTMS treatment resulted in the reduction of Aβ deposit in the hippocampus of AD mouse models [ 8 , 47 , 65 ]. Although previous studies have shown that rTMS may suppress the expression of APP and APP cleavage enzyme, β-secretase 1 (BACE1), therefore reduce the production and processing of Aβ in the AD mouse brains [ 27 ], however, merely reducing Aβ production may not be sufficient for the pathological improvement and cognitive benefits observed in rTMS-treated AD animal models and patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…51 Similarly, repetitive transcranial magnetic stimulation (rTMS) alleviates AD via promoting autophagy and reducing apolipoprotein E (APOE). 52 Furthermore, an in vitro model of AD revealed that β-asarone (derived from Acorus tatarinowii Schott) effectively counters those proteins implicated in AD pathogenesis including amyloid-beta precursor protein (APP), presenilin-1 (PSEN1/PS-1), beta-secretase 1 (BACE1), and Aβ via potentiating autophagy, which is demonstrated by LC3-II and BECN1 upregulation. 53 Moreover, in the SAMP8 mouse AD model, treatment with Yishen Huazhuo decoction enhanced Aβ removal via upregulation of BECN1 and downregulation of MTORC1 and promoted autophagosome formation, resulting in enhanced autophagy.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, identifying the specific autophagy failure is imperative to the development of therapeutic strategies [129]. Induction of autophagy reduces the levels of both the soluble and aggregated species in AD models and is associated with beneficial effects [130][131][132][133][134][135]. Many autophagy enhancing molecules have been developed [76,77] and their therapeutic effects have been extensively reviewed previously [136,137].…”
Section: Autophagy Therapeutics For Admentioning
confidence: 99%